Political independence, operational impartiality, and the effectiveness of anti-corruption agencies. Issue 1 (5th January 2015) - Jon S.T. Quah, Dr; Chilik Yu, Professor; Gregory, Robert
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This purpose of this paper is to discuss the relationship between political independence and operational impartiality in regard to the effectiveness of anti-corruption agencies (ACAs). Against this background of western orthodoxy, it asks whether a non-western country with high levels of corruption (Vietnam being an example) can find another pathway in its efforts to effectively combat corruption. Design/methodology/approach – An exercise in qualitative conceptual clarification and theoretical speculation, drawing upon practical examples. Findings – It is argued that it is important to distinguish between de jure and de facto political independence, and that neither can be fully understood unless they are considered in relationship to other key values, particularly operational impartiality, public accountability, and systemic legitimacy, and in the context of bureaucratic politics. There is little coherent theoretical knowledge available about the relationships among these variables. Such values are central to western notions of "good government" but are much less institutionalised in non-western jurisdictions with high levels of corruption. The question is raised: can such countries, Vietnam being one example, develop effective anti-corruption strategies which because of the nature of their own political system, cannot depend on political independence for its ACAs? Originality/value – Attention is drawn to some conceptual and putatively theoretical issues relating to the effectiveness of ACAs, and which have received little explicit attention in the relevant academic literature.